Effect of age of seedlings at staggered planting and nitrogen rate on the growth and yield of transplant Aman rice - Luna, MA; Sarkar, MAR; Uddin, MR; Sarker, UK (Journal of the Bangladesh Agricultural University, 2017)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during July to December 2015 to find out the effect of age of seedlings at staggered planting and nitrogen rate on the growth and yield of transplant Aman rice (cv. BRRI dhan46). The experiment comprised three ages of seedlings viz. 30, 45 and 60-day old and six nitrogen rate viz. 0, 40, 60, 80, 100 and 120k kg N ha1. The experiment was laid out in a Randomized Complete Block Design with three replications. The effect of age of seedlings and nitrogen rates and their interaction were significant on yield and yield contributing characters of transplant Aman rice. The highest plant height, total dry matter production hill1 and leaf area index were recorded in 30-day old seedlings with 80 kg N ha1. Grain yield gradually increased with the use of relatively younger seedlings and 30-day old seedlings produced the highest number of effective tillers hill1 (5.34), grains panicle1 (110.9), 1000-grain weight (24.60 g), grain yield (4.06 t ha1) and straw yield (5.17 t ha1). In case of nitrogen rate, 80 kg N ha1 produce the highest grains panicle1 (113.1), 1000-grain weight (25.39 g), grain yield (4.37 t ha1) and straw yield (5.59 t ha1). In interaction, 30-day old seedlings with 80 kg N ha1 produced the highest effective tillers hill1 (6.22), grains panicle1 (124.1), 1000-grain weight (26.91g), grain yield (4.71 t ha1) and straw yield (6.16 t ha1). Therefore, 30-day old seedlings with 80 kg N ha1 appeared as the promising technique to obtain the highest grain yield. It was also observed that under adverse situation delaying in transplanting may be continued up to 15 September with aged seedlings (60-day old) from the same source and application of nitrogen ranging from 100120 kg ha1 to obtain grain yield ranging from 3.84.0 t ha1. J. Bangladesh Agril. Univ. 15(1): 21-25, January 2017